Penggunaan Aplikasi TikTok sebagai Media Menyebarluaskan Informasi (Studi Kasus Pengelolaan Akun TikTok @pikiranrakyat) - Muhtarom, Syifa Zahra Aina (Annaba: Jurnal Ilmu Jurnalistik, 2020)
This study aims to determine the information management process carried out by the Social Media Division of Pikiran Rakyat Media Network (PRMN), the considerations for using the TikTok application, and the content criteria used by the Pikiran Rakyat TikTok account in disseminating information. The method used in this study is a case study method which is supported by the theory of diffusion of innovation and is associated with the immersion journalism approach technique regarding the approach process taken by one media to another. The results of this study indicate that the information management process begins with information seeking, management in the form of checking and editing of pictorial videos before finally being published on the Pikiran Rakyat TikTok account. The content criteria used on the Pikiran Rakyat TikTok account prioritizes information that is currently viral for publication.